THE MASS MEDIA AND PERSUASION - Vlera Ejupi; Liljana Siljanovska; Arburim Iseni (European Scientific Journal, ESJ, 2014)
In democratic societies, the media today have a complex relation with the sources of power and the political system. Firstly, they should emit information and attitudes independent from the government and interests of power, secondly, those with interests promote news and information closely related with the political parties and other groups. Hence, there has always been a close relation between the mass communication and the product of politics. In the relation between politics and the media the good informative function is very evident. As a part of the media reality, communication contents do not only transfer messages and information from the political factors, but they also analyze, select, make comments, give their own opinion and share attitudes on them. Media effects on politics are realized through manipulative and propagandistic techniques of persuasion, contrary to the professional standards and criteria of the functioning of the mass media communication.